Assessing resiliency in Canadians experiencing social vulnerability: Psychometric properties of the CUPS Resiliency Interview Schedule and Resiliency Questionnaire. (22nd October 2020) - Perry, Robert; Ginn, Carla; Donnelly, Carlene; Benzies, Karen
Abstract: Deficit models of care for clients experiencing social vulnerability have become increasingly unsustainable; and there is a shift towards models of care that promote and protect resiliency for lifelong health. We defined clients as socially vulnerable if they were living with poverty, mental health problems and addictions, disability, and social isolation. Scales to measure outcomes of resiliency‐focused programming have limited reliability and have not been validated with vulnerable populations. The aim of this study was to develop and conduct preliminary psychometric assessment of two measures: CUPS (formerly Calgary Urban Project Society) Resiliency Interview Schedule (RIS) and Resiliency Questionnaire (RQ) for adults experiencing social vulnerability. To engage clients who were seeking integrated services at a social services agency, we developed the RIS and accessed data collected between April 2017 and December 2018. In a structured intake interview, the client and staff prioritised goals and identified resiliency in three domains: (a) economic, (b) social‐emotional, and (c) health. On average, clients ( N = 545) who completed the CUPS‐RIS were 45.9 years old ( SD = 12.62). For the CUPS‐RIS, Cronbach's alphas at intake and outcome assessments were 0.80. Exploratory factor analysis demonstrated a four‐factor solution with two unexpected results: executive functioning/self‐regulation loaded with mental and physical health, and client education failed to load on any factor. We found significant improvements between client intake and outcome measurement points on eight of 12 sub‐domains. As a brief self‐report measure of resiliency, we developed the CUPS‐RQ and accessed data collected between November 2018 and May 2019. Clients ( N = 29) who completed the CUPS‐RQ concurrently with the Resilience Research Centre‐Adult Resilience Measure (RRC‐ARM) were, on average, 42.46 years old ( SD = 12.87). The CUPS‐RQ was correlated with RRC‐ARM, r = 0.819. In preliminary psychometric assessment, the CUPS‐RIS and CUPS‐RQ demonstrated satisfactory reliability and validity and show promise as measures of resiliency for agencies serving clients experiencing social vulnerability.